2008
DOI: 10.1617/s11527-008-9388-4
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation in cementitious material containing artificial distributed damage

Abstract: The propagation of ultrasonic pulses through highly inhomogeneous mortar is discussed in this paper. The inhomogeneity is introduced by light plastic inclusions in different volume contents to simulate distributed damage. Wave propagation in such media becomes dispersive and therefore, although pulse velocity is influenced, other easily measured features are much more indicative of the inclusion content. These features can certainly improve characterization since they include information from the whole wavefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…While methods for estimating stable crack growth rate based on AE signals are well established, estimating crack damage at the smallest possible scale is most desirable. This idea has motivated researchers to better understand wave dynamics of AE signals within single crystals [18][19][20][21] and polycrystalline materials [11,12,15,[22][23][24][25][26][27][28][29][30] (see [31] for further discussion on past AE literature). From these studies, researchers concluded that AE activity is present during initial damage due to dislocation motion and microcracks, and various AE features can be correlated to damage.…”
Section: Introductionmentioning
confidence: 99%
“…While methods for estimating stable crack growth rate based on AE signals are well established, estimating crack damage at the smallest possible scale is most desirable. This idea has motivated researchers to better understand wave dynamics of AE signals within single crystals [18][19][20][21] and polycrystalline materials [11,12,15,[22][23][24][25][26][27][28][29][30] (see [31] for further discussion on past AE literature). From these studies, researchers concluded that AE activity is present during initial damage due to dislocation motion and microcracks, and various AE features can be correlated to damage.…”
Section: Introductionmentioning
confidence: 99%
“…Such mean errors are quite accurate, considering the properties variation that can be found in these materials. The effectiveness of this approach has been recognized by several authors [19][20][21]. Recently, our research group has proposed a multiphase approach of a self-consistent multiple scattering model to describe the influence of the size and volume fraction of aggregates on cementitious materials, as well as the interaction, contribution, and influence entrapped air voids together with the aggregates on frequency-dependent parameters such as the phase velocity and the attenuation coefficient [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Another is that it can be measured using very simple equipment, without the need of delicate waveform analysis, and therefore, it has been used for more than 50 years. This leads to the next advantage which is the long‐established, although rough, correlations with concrete strength [7–10]. Nowadays, waveform acquisition is standard to most of the available equipment for ultrasonic testing.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental measurements were conducted in cementitious material containing small light inclusions to simulate distributed damage in different volume contents. It is seen that the inclusions influence pulse velocity but they have stronger influence on other parameters like velocity dispersion (frequency dependence) as well as high attenuation for high frequencies [10, 11] because of extensive scattering. As wave propagation in material with damage is an extremely complicated subject, numerical simulations are used to shed light and understand the contribution of different parameters (frequency, orientation of cracks) on the finally measured wave features.…”
Section: Introductionmentioning
confidence: 99%